Surgery Is the Last Resort for Huge Scrotal Lymphedema: A Series of Challenging Cases - ElKiran, Yasser M.; Elshafei, Amr M.; Abdelgawad, Mohamed S.; Kamel, Mohammed F.; Sharaf-Eldeen, Hesham A.; Abdelmaksoud, Mohammed A. (Archives of Plastic Surgery, 2023)
We aim to provide our surgical techniques, and outcomes of functional scrotal reduction procedures with complete preservation of the genitourinary original anatomy in a simple way without using complicated skin grafting or skin advancement flaps in Patients with huge and long-standing scrotal lymphedema 18 patients ages ranged from 14-65 with a median of 30 years. Functional scrotal and penoscrotal reduction was attained in all cases, without distortion of the genitourinary anatomy and without the need for advancement, rotational or free flaps, maximal scrotal diameter was reduced from median of 61[48-92] cms to a median of 25[21–29] cms (P<0.0001) and remained almost unchanged at the end of the follow up period 26[22-34] cms (P<0.0001). Sexual performance and voiding capacity were improved in all patients, testicular vascularity was unaffected and the Glasgow Benefit Inventory (GBI) for the quality of life showed marked enhancement in the total 55.5[50–72], general 55.5[50–72], social 100[50–100] and physical 16.6[16–33] points subscales. According to our experience, surgery remains the gold standard treatment for management of huge scrotal lymphedema, successful preservation of the genitourinary functions can be attained despite the size in most cases with excellent cosmoses.
Keywords: lymphedema; genitalia; scrotal swelling